2020
DOI: 10.1016/j.ymgmr.2020.100679
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in elderly patients with Morquio a syndrome receiving enzyme replacement therapy - experience in a Colombian center

Abstract: Introduction Mucopolysaccharidosis type IV A (MPS IVA) or Morquio A syndrome is an autosomal recessive lysosomal storage disease caused by GALNS gene mutations that lead to a deficiency of the N -acetylgalactosamine-6-sulfate sulfatase enzyme and the accumulation of two glycosaminoglycans in cell lysosomes, namely, chondroitin and keratan sulfate. Objective To present two female patients with Morquio A syndrome in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
2
0
2
Order By: Relevance
“…Доказано, что под влиянием этой терапии снижается уровень кератансульфата в моче, улучшаются показатели в тестах с 6-минутной ходьбой и 3-минутным подъемом по лестнице, функциональные тесты легких, мышечный тонус и снижается уровень болевых ощущений у пациентов [11,14,15]. Есть данные, что проведение ферментозаместительной терапии даже в пожилом возрасте спустя 18 мес от ее старта приводило к увеличению подвижности суставов и двигательной активности в целом [16]. В случае ранней диагностики заболевания и старта лечения в первые годы жизни терапия более эффективна и мультисистемных необратимых поражений можно избежать.…”
Section: Discussionunclassified
“…Доказано, что под влиянием этой терапии снижается уровень кератансульфата в моче, улучшаются показатели в тестах с 6-минутной ходьбой и 3-минутным подъемом по лестнице, функциональные тесты легких, мышечный тонус и снижается уровень болевых ощущений у пациентов [11,14,15]. Есть данные, что проведение ферментозаместительной терапии даже в пожилом возрасте спустя 18 мес от ее старта приводило к увеличению подвижности суставов и двигательной активности в целом [16]. В случае ранней диагностики заболевания и старта лечения в первые годы жизни терапия более эффективна и мультисистемных необратимых поражений можно избежать.…”
Section: Discussionunclassified
“…Two additional articles (L. Wang et al, 1999 ; Whybra et al, 2012 ), published before 2014, that were not included in the previous update were recovered by comparison of our list of variants with that reported by HGMD Professional 2020.1. Moreover, two other articles (Erazo‐Narváez et al, 2020 ; Ficicioglu et al, 2020 ) were recently published and, owing to the timing of the present article submission, were not included in the whole analysis. Ficicioglu et al ( 2020 ) reported three African American siblings who were compound heterozygotes for c.611A>G [p.(Asn204Thr)] and c.964G>C [p.(Ala322Pro)].…”
Section: Variantsmentioning
confidence: 99%
“…Ficicioglu et al ( 2020 ) reported three African American siblings who were compound heterozygotes for c.611A>G [p.(Asn204Thr)] and c.964G>C [p.(Ala322Pro)]. Erazo‐Narváez et al ( 2020 ) reported two Colombian women carrying the variants c.491A>C [p.(Asn164Thr)] and c.901G>T [p.(Gly301Cys)]. All of these variants had been previously described, with the exception of c.964G>C, which has been included in the present list of GALNS unique variants (Table S2 ).…”
Section: Variantsmentioning
confidence: 99%
“…В настоящее время к возрасту 18 лет пациент имеет рост 122 см, что соответствует средним показателям для больных с синдромом Моркио. Следует отметить, что даже в случае терапии элосульфазой альфа у пожилых пациентов через 18 мес они смогли восстановить способность к самостоятельному хождению, отмечали уменьшение боли и усталости [21]. Полученные данные указывают на положительное влияние ферментозаместительной терапии, подтверждают важность раннего начала лечения и необходимость его продолжения в течение всей жизни пациента [34].…”
Section: клинические случаиunclassified